Assessing chelators’ efficiency in removing iron stains from textiles using X-ray fluorescence: Preliminary results - Kolovi, S.; Tsompopoulou, E.; Mergia, K.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2019)
The removal of iron corrosion products is considered necessary in textile conservation and it is usually undertaken by the application of chelating agents. The efficacy of the various chelating agents is not always known and therefore, non-destructive analytical methods are often used to assess their performance. In the present work, Energy Dispersive X-ray fluorescence (EDXRF) spectroscopy was used to determine iron in textile samples before and after cleaning. It was shown that EDXRF provides a simple, rapid, non-destructive technique to determine the efficiency of iron removal after conservation treatment in textiles.